The Global Diffusion of Stewardship Codes - Dionysia Katelouzou; Mathias Siems (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2020)
n today's world, the transfer of laws and regulations between different legal systems is commonplace. The global spread of stewardship codes in recent years presents a promising, but yet untested, terrain to explore the diffusion of such norms. This paper aims to fill this gap. Employing the method of content analysis and using information from 41 stewardship codes enacted between 1991 and 2019, we systematically examine the formal diffusion of these stewardship codes. While we find support for the diffusion story of the UK as a stewardship norm exporter, especially in former British colonies in Asia, we also find evidence of diffusion from transnational initiatives, such as the EFAMA and ICGN codes, as well as regional clusters. We also show that the UK Stewardship Code of 2020 now deviates from these current models; thus, it remains to be seen how far a second round of exportation of the revised UK model into the transnational arena will follow.
urn:nbn:de:hebis:30:3-616503
Keywords: C38; K22; 330; institutional investors; stewardship codes; diffusion of norms; legal transplants; content analysis